Customer satisfaction analysis on general banking of Export Import Bank of Bangladesh Limited (EXIM) - Sheikh, Tania (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.